Incomplete separability of Antarctic plate rotation from glacial isostatic adjustment deformation within geodetic observations. Issue 1 (20th November 2015) - King, Matt A.; Whitehouse, Pippa L.; van der Wal, Wouter
Abstract: Geodetic measurements of Antarctic solid Earth deformation include signals from plate rotation and glacial isostatic adjustment (GIA). Through simulation, we investigate the degree to which these signals are separable within horizontal GPS site velocities that commonly define plate rotation estimates and that promise new constraints on models of GIA. Using a suite of GIA model predictions that incorporate both 1-D and 3-D Earth rheologies, we show that, given the present location of GPS sites within East Antarctica, unmodelled or mismodelled GIA signal within GPS velocities produces biased estimates of plate rotation. When biased plate rotation is removed from the GPS velocities, errors as large as 0.8 mm yr −1 are introduced; a value commonly larger than the predicted GIA signal magnitude. In the absence of reliable forward models of plate rotation or GIA then Antarctic geodetic velocities cannot totally and unambiguously constrain either process, especially GIA.